2013
DOI: 10.1002/aic.14321
|View full text |Cite
|
Sign up to set email alerts
|

Filtered and heterogeneity‐based subgrid modifications for gas–solid drag and solid stresses in bubbling fluidized beds

Abstract: Two different approaches to constitutive relations for filtered two-fluid models (TFM) of gas-solid flows are deduced. The first model (Model A) is derived using systematically filtered results obtained from a highly resolved simulation of a bubbling fluidized bed. The second model (Model B) stems from the assumption of the formation of subgrid heterogeneities inside the suspension phase of fluidized beds. These approaches for the unresolved terms appearing in the filtered TFM are, then, substantiated by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
108
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 44 publications
2
108
0
Order By: Relevance
“…For the numerical simulation we use the commercial CFD-solver FLUENT (version 14), whereby we implemented the poly-disperse drag force [20] and the coarse grained solid stresses of [2][3][4]23] by using user defined functions. For the discretization of all convective terms a second-order upwind scheme is used.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the numerical simulation we use the commercial CFD-solver FLUENT (version 14), whereby we implemented the poly-disperse drag force [20] and the coarse grained solid stresses of [2][3][4]23] by using user defined functions. For the discretization of all convective terms a second-order upwind scheme is used.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…However, these previous studies did not include the impact of segregation. Since these models are well documented in our previous studies [2][3][4]6], we do not repeat the details here.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The model has also been subjected to extensive tests from outside and to various modifications to meet the requirements of the specific problems they studied. It has been modified (i) to simulate CFB combustors [114,115], calcium looping for CO 2 capture in a lignite fired power plant [116], CFB carbonator [117] and gas desulfurization in a CFB riser [118]; (ii) to address the anisotropic characteristics of EMMS drag model [119]; (iii) to test the effects of using different particle cluster size correlations [120,121]; (iv) to model the effective interphase drag force of bubbling fluidization [122][123][124]; (v) to formulate an EMMS drag model that is conceptually consistent with the so-called type A two-fluid model and its applications [125][126][127][128][129][130]; (iv) to formulate another version by assuming the particle in dilute phases are in dilute limit and the particles in dense phase satisfy the Richardson-Zaki correlation [131,132]. Recent studies have shown that the EMMS drag model can also be used in Eulerian-Lagrangian simulations [133][134][135][136][137].…”
mentioning
confidence: 99%